(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
This study aimed to analyze factors affecting the loan disbursement in commercial banks in Indonesia from 2017 to 2022. The independent variables analyzed were Third-Party Funds (TPF), Non-Performing Loan (NPL) Capital Adequacy Ratio (CAR), BI Rate, Gross Domestic Product (GDP), and IDR/USD Exchange Rate. The study of factors affecting the loan disbursement in commercial banks used the quantitative approach with Error Correction Model (ECM). The results of the study were as follows. (1) TPF had a significant positive effect on the loan disbursement in the long term and the short term. (2) NPL had a significant negative effect on the loan disbursement in the long term and short term. (3) CAR had a significant negative effect on the loan disbursement in the long term and short term. (4) BI Rate did not have a significant effect on the loan disbursement in the long term and short term. (5) GDP in the long term had a significant positive effect on the loan disbursement, but it did not have a significant effect in the short term. (6) IDR/USD Exchange Rate had a significant positive effect on the loan disbursement in the long term and short term.